Comparação do método químico e método a plasma no preparo de nanocompósitos de prata e nanocelulose - Matsuda, Larissa Mariana Mendes (Universidade Federal de São Carlos, 2020)
Cellulose, being a biodegradable material, flexible and with good mechanical resistance, has been attracting great interest in studies, as it is a biopolymer from a renewable source and widely available in nature. It can be used in several applications, such as in the textile, paper and packaging industries, in the production of sensors and biosensors and as a matrix in composites. In this context, the present work aims to manufacture and characterize nanocellulose (NC) nanocomposites containing silver. Two routes were investigated: (i) composite nanocellulose films containing silver nanoparticles (AgNPs) chemically synthesized and (ii) incorporation of silver through the sputtering process from silver nitrate powder (AgNO3). The nanocomposite films were made from a suspension of nanocellulose and AgNPs. The AgNPs were synthesized by chemical reduction with sodium citrate (Na3C6H5O7) and incorporated into the NC films using a vacuum filtration system. Another method used was the sputtering process, from the silver salt placed in the lower sample holder of the plasma reactor. For the treatment, the use of argon gas and a mixture of argon and oxygen (90% and 10%, respectively) was investigated. The plasma was excited by the application of radio frequency of 13.56 MHz, power from 150 to 200 W, and treatment time from 30 to 90 min, with a working pressure of 14.9 to 8.8 Pa. After deposition, the samples were characterized with X-ray diffraction (XRD), profilometry, absorption in the Ultraviolet and Visible region (UV-Vis), scanning electron microscopy (SEM) and X-ray dispersive energy spectroscopy (EDS), angle of microbiological contact and analysis. The results obtained for the XRD were similar in the two routes studied showing the same diffraction angles at 14, 16 and 22 °, with the profilometer it was observed the formation of a thin film in the glass samples, the data obtained in the UV analysis -Vis indicate absorption bands similar to the chemical route, for the characterization in SEM, there was also similarity, with observation of homogeneity in the morphology of all samples synthesized through the chemical route, whereas for the plasma route there was a dependent morphological change treatment parameters. The analysis by the EDS technique, performed for the chemical route presents a low percentage of silver, while the plasma route indicates a variation in the silver content on the surface of the membranes from 3.6 to 31% of silver depending on the parameters. In the microbiological analysis, the chemical route showed an average inhibition halo of 7.4 mm for Staphylococcus aureus and 7.8 mm for Pseudomonas aeruginosa, and for the test performed for the plasma route, no growth of bacterial colonies was observed on the plates indicating the antimicrobial activity of nanocomposite films under T5 and T6 conditions. Therefore, the results confirm the incorporation of silver by the Sputtering method from silver nitrate, as well as the bactericidal activity in agreement with the results of the nanocomposites made with the chemical synthesis of the AgNPs.
Comparison of the chemical method and the plasma method in the preparation of silver nanocomposites and nanocellulose
Keywords: Deposição a plasma.; Prata.; Efeito antimicrobiano.; Plasma deposition.; Antimicrobial effect.; Silver.; CIENCIAS EXATAS E DA TERRA::FISICA; ENGENHARIAS::ENGENHARIA BIOMEDICA::ENGENHARIA MEDICA::BIOMATERIAIS E MATERIAIS BIOCOMPATIVEIS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::POLIMEROS, APLICACOES; OUTROS; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::PAPEL E CELULOSE